Food and Feed Safety of NS-B5ØØ27-4 Omega-3 Canola (Brassica napus): A New Source of Long-Chain Omega-3 Fatty Acids - MacIntosh, Susan C.; Shaw, Megan; Connelly, Michael; Yao, Zhuyun June (Frontiers in Nutrition, 2021)
DHA canola, a genetically engineered Brassica napus (OECD Unique Identifier NS-B5ØØ27-4), has been developed as one of the first land-based production systems for omega-3 long-chain polyunsaturated fatty acids (LCPUFA), whose health benefits are well established. Yet, the marine sources of these nutrients are under high pressures due to over-fishing and increasing demand. DHA canola is a plant-based source for these essential fatty acids that produces a high level of docosahexaenoic acid (DHA). This terrestrial system allows for sustainable, scalable and stable production of omega-3 LCPUFA that addresses not only the increasing market demand, but also the complex interplay of agriculture, aquaculture and human nutrition. The vector used to produce the desired oil profile in DHA canola contains the expression cassettes of seven genes in the DHA biosynthesis pathway and was specifically designed to convert oleic acid to DHA in canola seed. The characterization and safety evaluation of food and feed produced from DHA canola are described and supported by a detailed nutritional analysis of the seed, meal and oil. Aside from the intended changes of the fatty acid profile, none of the other compositional analytes showed biologically meaningful differences when compared to conventional canola varieties. In addition, the meal from DHA canola is nutritionally equivalent to conventional canola meal. Further evidence of nutritional value and safety of DHA canola oil have been confirmed in fish feeding studies. Given that most human populations lack sufficient daily intakes of omega-3 LCPUFA, a dietary exposure assessment is also included. In conclusion, the results from these studies demonstrate it is safe to use products derived from DHA canola in human foods, nutraceuticals or animal feeds.